Intestine-selective reduction of Gcg expression reveals the importance of the distal gut for GLP-1 secretion - Brandon L. Panaro; Bernardo Yusta; Dianne Matthews; Jacqueline A. Koehler; Youngmi Song; Darleen A. Sandoval; Daniel J. Drucker (Elsevier, 2020)
Objective: Glucagon-like peptide-1 is a nutrient-sensitive hormone secreted from enteroendocrine L cells within the small and large bowel. Although GLP-1 levels rise rapidly in response to food ingestion, the greatest density of L cells is localized to the distal small bowel and colon. Here, we assessed the importance of the distal gut in the acute L cell response to diverse secretagogues. Methods: Circulating levels of glucose and plasma GLP-1 were measured in response to the administration of L cell secretagogues in wild-type mice and in mice with (1) genetic reduction of Gcg expression throughout the small bowel and large bowel (GcgGut−/-) and (2) selective reduction of Gcg expression in the distal gut (GcgDistalGut−/-). Results: The acute GLP-1 response to olive oil or arginine administration was markedly diminished in GcgGut−/- but preserved in GcgDistalGut−/- mice. In contrast, the increase in plasma GLP-1 levels following the administration of the GPR119 agonist AR231453, or the melanocortin-4 receptor (MC4R) agonist LY2112688, was markedly diminished in the GcgDistalGut−/- mice. The GLP-1 response to LPS was also markedly attenuated in the GcgGut−/- mice and remained submaximal in the GcgDistalGut−/- mice. Doses of metformin sufficient to lower glucose and increase GLP-1 levels in the GcgGut+/+ mice retained their glucoregulatory activity, yet they failed to increase GLP-1 levels in the GcgGut−/- mice. Surprisingly, the actions of metformin to increase plasma GLP-1 levels were substantially attenuated in the GcgDistalGut−/- mice. Conclusion: These findings further establish the importance of the proximal gut for the acute response to nutrient-related GLP-1 secretagogues. In contrast, we identify essential contributions of the distal gut to (i) the rapid induction of circulating GLP-1 levels in response to pharmacological selective agonism of G-protein-coupled receptors, (ii) the increased GLP-1 levels following the activation of Toll-Like Receptors with LPS, and iii) the acute GLP-1 response to metformin. Collectively, these results reveal that distal gut Gcg + endocrine cells are rapid responders to structurally and functionally diverse GLP-1 secretagogues.